PENGARUH RISIKO FISIK DAN RISIKO PSIKOLOGIS TERHADAP NIAT BERKUNJUNG KEMBALI YANG DIMEDIASI OLEH CITRA KOGNITIF PADA WISATAWAN DI KOTA BANDA ACEH - Frillyanti Chairunnisa; M. Ridha Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to measure the Influence of Physical Risk and Psychological Risk to Revisit Intention with Cognitive Image as a Mediating Variable on Travelers in Banda Aceh City. The sample used in this study is the tourists who have been and are visiting the city of Banda Aceh, amounting to 310 respondents. Data collection equipment used in this research is questionnaire. The sampling technique used is Purposive Sampling. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved. Based on the results of HLM analysis, it indicates that Physical Risk affects Revisit Intention, Psychological Risk Affects Revisit Intention, Physical Risk Affects Cognitive Image, Psychological Risk Affects Cognitive Image, Cognitive Image Affects Revisit Intention, Cognitive Image mediates the relationship between Physical Risk to Revisit Intention, and Cognitive Image mediates the relationship between Psychological Risk to Revisit Intention.